2018
DOI: 10.1590/fst.09317
|View full text |Cite
|
Sign up to set email alerts
|

Honey and bee pollen produced by Meliponini (Apidae) in Alagoas, Brazil: multivariate analysis of physicochemical and antioxidant profiles

Abstract: (Dnline) 2 Materials and methods 2.1 Samples of honey and bee pollen from meliponini species Different samples of honey (n = 31) and bee pollen (n = 25), respectively from seven stingless bees species: Melipona asilvai Moure (1971); M. quadrifasciata anthidioides Lepeletier (1836); M. scutellaris Latreille (1811); M. subnitida Ducke (1910); Frieseomelitta varia Lepeletier (1836); Tetragona clavipes Fabricius (1804) and Plebeia sp., and six of such species (all the above mentioned less F. varia) were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
3
25
2
2
Order By: Relevance
“…Bárbara et al (2015) reported similar results indicating that the mean moisture, ash, pH, titratable acidity levels of 21 bee pollen (Melipona mandacaia) samples collected from two different regions of Bahia and Brazil were 36.0%, 4.9%, 3.49, and 146 meq•kg −1 , respectively. Duarte et al (2018) found similar pH values for bee pollen produced in the Alagoas, Northeast region of Brazil by M. subnitida and T. clavipes respectively 4.9 and 5.9.…”
Section: Physicochemical Propertiessupporting
confidence: 55%
“…Bárbara et al (2015) reported similar results indicating that the mean moisture, ash, pH, titratable acidity levels of 21 bee pollen (Melipona mandacaia) samples collected from two different regions of Bahia and Brazil were 36.0%, 4.9%, 3.49, and 146 meq•kg −1 , respectively. Duarte et al (2018) found similar pH values for bee pollen produced in the Alagoas, Northeast region of Brazil by M. subnitida and T. clavipes respectively 4.9 and 5.9.…”
Section: Physicochemical Propertiessupporting
confidence: 55%
“…The lowest electrical conductivity values were recorded in honey samples (142.8-198.8 µS/cm). Other researchers reported that the electrical conductivity of Brazilian honey ranged from 300 to 1400 µS/cm [28]. The observed differences allowed to assume that electrical conductivity, together with other physicochemical properties of bee products, depend on biological and geographical origin.…”
Section: Physicochemical Properties Of Bee Pollen and Other Bee Productsmentioning
confidence: 90%
“…Bee pollen samples distinguished by the highest pH values (4.30-5.22), while the lowest pH values ranging from 3.57 to 4.06 were determined in royal jelly samples. Other studies in literature showed that the pH values of bee pollen varied from 4.3 to 5.9 [27,28], honey from 3.6 to 5.6 [21,29], propolis from 4.7 to 5.3 [21], beebread from 3.8 to 4.3 [12,13] and royal jelly from 3.4 to 4.5 [30,31]. As it can be seen, the results of this research coincide with the data published by other authors.…”
Section: Physicochemical Properties Of Bee Pollen and Other Bee Productsmentioning
confidence: 95%
“…It has been reported that bee pollen is rich in phenolic compounds and it acts as a free radical scavenger and lipid peroxidation inhibitor originating from flavonoids it contains and it has antioxidant properties [30]. Duarte et al in their study to determine the physicochemical and antioxidant profiles of honey and pollen produced by honey bees (Apis mellifera scutellata) in Brazil, the highest total phenolics value in honey collected from natural areas was 1.36 mgGAEq/g and 21 mg in pollen [31]. In another study, the total phenolic content in honey has been reported as 15.84 mg/100 g [32].…”
Section: 1total Phenolicsmentioning
confidence: 99%